Point-slope form, Mathematics

The next special form of the line which we have to look at is the point-slope form of the line. This form is extremely useful for writing the equation of any line.  If we know that a line passes through the point (x1 , y1 ) and has a slope of m then the point-slope form of the  equation of the line is,

                                           y - y1 = m ( x - x1 )

Sometimes it is written as,

                                        y = y1 + m ( x - x1 )

As stated earlier this form is specifically useful for writing down the equation of a line so let's take a look at an example of this.

Posted Date: 4/6/2013 5:58:02 AM | Location : United States







Related Discussions:- Point-slope form, Assignment Help, Ask Question on Point-slope form, Get Answer, Expert's Help, Point-slope form Discussions

Write discussion on Point-slope form
Your posts are moderated
Related Questions
Let D(subscript12) = ({x,y : x^2 = e ; y^6 = e ; xy =(y^-1) x}) a) Which of the following subsets are subgroups of D(subscript12) ? Justify your answer. i) {x,y,xy,y^2,y^3,e}


Derivative for the trig function: We'll begin with finding the derivative of the sine function. To do this we will have to utilize the definition of the derivative. It's been wher

steps to draw direction or slope fields

A right triangle whose sides are 15 cm and 20 cm is made to revolve about its hypotenuse. Find the volume and surface area of the double cone so formed. (Ans : 3768cu.cm,1318.8

How many integers satisfy the inequality |10(x+1)/x^2+2x+3|=1? Solution) first thing thats not an inequality, and second thing its very easy if thats the question. the LHS = |10/

Inverse Sine : Let's begin with inverse sine.  Following is the definition of the inverse sine. y = sin -1 x         ⇔     sin y = x                for - ?/2 ≤ y ≤ ?/2 Hen

Our objective is solve the following fourth-order BVP: (a(x)u'' )'' = f (x) u(0) = u(1)=0 u(0)' = u(1)'=0 (a) Give the variational formulation of the above BVP. (b) Describe the

find the no of solution of 2*3*4*5*6*6

First, see that the right hand side of equation (2) is a polynomial and thus continuous. This implies that this can only change sign if this firstly goes by zero. Therefore, if the